Testing the efficiency of duckweed Lemna spp. in reducing the concentration of zinc and iron from the wastewater when increase biomass (Baghdad Science Journal, 2011)
The study searches for the possibility of using duckweed Lemna spp. to reduce the concentration of heavy metals (zinc and iron) in the wastewater of Baghdad by culturing two different densities of the plant with a fresh weights 5 and 10 g/l and without the plant under optimum uncontrolled conditions.The result showed that there was a significant differences at the possibility level of (p? 0.05) for the three treatments, as the highest percentages for zinc removal in the second day for the plant treatment of 5 g/l were 66.40%, while the highest percentage of iron removal were in the tenth days for the plant treatment 10 g/l were 80 %, and noticed that the increase of the heavy metals concentrations accumulated in the plant after being cultured in the wastewater compared to the concentration before it is cultured.Concluded from the study the superiority of the plant treatments in reducing the concentrations of heavy metals as well as the density of the plant cultured weight 10 g/l is very suitable to remove the heavy metals from the wastewater.